Production of mycobacterial cell wall glycopeptidolipids requires a member of the MbtH-like protein family - Tatham, Elizabeth (BioMed Central, 2012)
BACKGROUND: Glycopeptidolipids (GPLs) are among the major free glycolipid components of the outer membrane of several saprophytic and clinically-relevant Mycobacterium species. The architecture of GPLs is based on a constant tripeptide-amino alcohol core of nonribosomal peptide synthetase origin that is N-acylated with a 3-hydroxy/methoxy acyl chain synthesized by a polyketide synthase and further decorated with variable glycosylation patterns built from methylated and acetylated sugars. GPLs have been implicated in many aspects of mycobacterial biology, thus highlighting the significance of gaining an understanding of their biosynthesis. Our bioinformatics analysis revealed that every GPL biosynthetic gene cluster known to date contains a gene (referred herein to as gplH) encoding a member of the MbtH-like protein family. Herein, we sought to conclusively establish whether gplH was required for GPL production. RESULTS: Deletion of gplH, a gene clustered with nonribosomal peptide synthetase-encoding genes in the GPL biosynthetic gene cluster of Mycobacterium smegmatis, produced a GPL deficient mutant. Transformation of this mutant with a plasmid expressing gplH restored GPL production. Complementation was also achieved by plasmid-based constitutive expression of mbtH, a paralog of gplH found in the biosynthetic gene cluster for production of the siderophore mycobactin of M. smegmatis. Further characterization of the gplH mutant indicated that it also displayed atypical colony morphology, lack of sliding motility, altered capacity for biofilm formation, and increased drug susceptibility. CONCLUSIONS: Herein, we provide evidence formally establishing that gplH is essential for GPL production in M. smegmatis. Inactivation of gplH also leads to a pleiotropic phenotype likely to arise from alterations in the cell envelope due to the lack of GPLs. While genes encoding MbtH-like proteins have been shown to be needed for production of siderophores and antibiotics, our study presents the first case of one such gene proven to be required for production of a cell wall component. Furthermore, our results provide the first example of a mbtH-like gene with confirmed functional role in a member of the Mycobacterium genus. Altogether, our findings demonstrate a critical role of gplH in mycobacterial biology and advance our understanding of the genetic requirements for the biosynthesis of an important group of constituents of the mycobacterial outer membrane.